Diagnostic and prognostic role of protein and ultrastructural alterations at cell–extracellular matrix junctions in neoplastic progression of human oral malignancy. (3rd September 2022) - Dongre, Harsh Nitin; Mahadik, Snehal; Ahire, Chetan; Rane, Pallavi; Sharma, Shilpi; Lukmani, Fatima; Patil, Asawari; Chaukar, Devendra; Gupta, Sudeep; Sawant, Sharada Suhas
ABSTRACT: Despite advancements in technology and increase in favorable outcomes associated with oral cancer, early detection remains the most significant factor in limiting mortality. The current study aimed to develop early diagnostic and prognostic markers for oral tumorigenesis. Protein and ultrastructural alterations at cell-extracellular matrix (ECM) adhesion junctions were examined concurrently using immunohistochemistry (IHC) and transmission electron microscopy (TEM) on progressive grade of oral carcinomas (n = 285). The expression of hemidesmosome (HD) proteins-integrin β4, BP180, and laminin-5 increased in hyperplasia as compared to normal, and significantly increased further, as the disease progressed. TEM analysis in parallel tissues revealed a significant decrease in HD number and increase in the length of basal lamina (BL) in hyperplasia. With cancer progression, the severity of ultrastructural alterations increased gradually and significantly. Overexpression of HD proteins, decrease in HD number and increase in BL length significantly correlated with nodal metastasis, local recurrence, and recurrence-free survival of patients. Concurrent use of IHC and TEM can add value to early recognition of neoplastic changes in primary carcinomas of oral cavity. In this regard, altered expression of integrin β4 and laminin-5, loss of HDs, and increased BL length could offer criteria for early diagnosis and prognosis of oral malignancy.